Hubungan Pengetahuan Ibu Postpartum dengan Manfaat Rawat Gabung di RS Bhayangkara Banjarmasin Kalimantan Selatan - Fifin Diah Oktaviani; Anik Purwati (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2024)
Combined care is a care system where babies and mothers are treated in one unit. In its implementation, the baby must always be by the mother's side from birth until he returns home. The advantages of combined care are that it promotes the use of breast milk, emotional contact between mother and baby is established from an early age, mothers can learn to take care of babies and mothers can immediately report strange baby conditions they encounter. The purpose of this study is to determine the relationship between postpartum maternal knowledge and the benefits of combined care at Bhayangkara Hospital Banjarmasin, South Kalimantan. This research method uses a type of analytical descriptive research with data collection techniques using a cross sectional approach and the instrument used is a questionnaire. The population of this study is all postpartum mothers at Bhayangkara Hospital Banjarmasin with a sampling technique using accidental sampling, with a sample of 30 respondents. The results obtained from the bivariate analysis of the chisquare statistical test showed that the value of p = 0.000 > ? = 0.05. The results obtained were that most postpartum mothers had insufficient knowledge, namely 15 people (50%) with most of them having a high school education of 14 people (46.7%), and never carried out combined care as many as 19 people (63.3%). The conclusion shows that most postpartum mothers have less knowledge about the benefits of combined care at Bhayangkara Hospital Banjarmasin. This shows that a person's level of education also affects the level of mother's knowledge.